The Roles of General Election Commission and General Election Supervisory Board for a Democratic Election - Suparman Marzuki (Fakultas Hukum Universitas Islam Indonesia, 2008)
To build a strong and reliable democratic institution, is a time consuming process which also requires a long patience. Accordingly, three pillars of General Election Commission (KPU), namely, structural independency, functional independency and personal independency, shall be consistently kept up and maintained.Keywords: General Election Commission, General Election Supervisory Board, Democratic